Polystyrene microbeads influence lipid storage distribution in C. elegans as revealed by coherent anti-Stokes Raman scattering (CARS) microscopy. (1st February 2022) - Fueser, Hendrik; Pilger, Christian; Kong, Cihang; Huser, Thomas; Traunspurger, Walter
Abstract: The exposure of Caenorhabditis elegans to polystyrene (PS) beads of a wide range of sizes impedes feeding, by reducing food consumption, and has been linked to inhibitory effects on the reproductive capacity of this nematode, as determined in standardized toxicity tests. Lipid storage provides energy for longevity, growth, and reproduction and may influence the organismal response to stress, including the food deprivation resulting from microplastics exposure. However, the effects of microplastics on energy storage have not been investigated in detail. In this study, C . elegans was exposed to ingestible sizes of PS beads in a standardized toxicity test (96 h) and in a multigeneration test (∼21 days), after which lipid storage was quantitatively analyzed in individual adults using coherent anti-Stokes Raman scattering (CARS) microscopy. The results showed that lipid storage distribution in C. elegans was altered when worms were exposed to microplastics in form of PS beads. For example, when exposed to 0.1-μm PS beads, the lipid droplet count was 93% higher, the droplets were up to 56% larger, and the area of the nematode body covered by lipids was up to 79% higher than in unexposed nematodes. The measured values tended to increase as PS bead sizes decreased. Cultivating the nematodes for 96 h under restricted food conditions in the absence of beads reproduced the altered lipid storage and suggested that it was triggered by food deprivation, including that induced by the dilutional effects of PS bead exposure. Our study demonstrates the utility of CARS microscopy to comprehensively image the smaller microplastics (<10 μm) ingested by nematodes and possibly other biota in investigations of the effects at the level of the individual organism. Graphical abstract: Image 1 Highlights: Lipids and microbeads were imaged by coherent anti-Stokes Raman scattering (CARS). Polystyrene beads altered lipid storage distribution as revealed by CARS microscopy. Lipid storage distribution tended to increase as bead sizes decreased. Cultivating nematodes at low food conditions reproduced altered lipid storage. Label-free CARS microscopy can track minute microplastics ingested by biota.